AB0191 Frequency of Antibodies Against α-Fodrin in Patients with Primary SjÖgren's Syndrome. (9th June 2015) - Velez, S.; Zazzetti, F.; Schiel, A.; Rivero, M.; Khoury, M.; Duartes Noe, D.; Barreira, J.C.
Abstract : Background: The continuous overexpression of B lymphocytes in Primary Sjögren's syndrome (pSS) produces a variety of autoantibodies, like anti-Ro/SS-A or anti-La/SS-B, required for the diagnosis, albeit others pose an uncertain clinical significance. According to recent data, anti-α-fodrin antibodies could be used as a reliable diagnostic marker in those patients seronegative to other antibodies. Objectives: Thus, the aim was to determine the frequency of anti-α-fodrin antibodies in patients withpSS and describe their clinical association. Methods: Forty patients, who fulfilled the 2002 American-European criteria for pSS and 23 controls matched for age and gender, were included. Those who had received any biologic therapy were excluded. Demographic data, clinical manifestations and laboratory findings were recorded. Minor salivary gland biopsies were considered positive according to Chisholm scale. Anti-α-fodrin antibodies were determined utilizing an ELISA immunoassay (Orgentec-Germany) according to the manufacturer's instructions. Mann-Whitney test was used to compare numeric variables, and chi-square or Fisher's test for categorical. A p value of 0.05 was considered statistically significative. Confidence intervals (CI) were estimated for a value of 95%. Results: Of the 40 patients with pSS, 22 (55%) tested positive for anti-α-fodrin antibodies, with a sensitivity of 100% (CI =40% - 70%) and a specificity of 56% (CI =40% - 70%). All controls resulted negative (p<0.0001). Gender was 91% female for the positive group (2/22) and 100% for the negative group. Age at diagnosis was 57.6±12 years (range =30-85) for the positive group, and 59.3±12.9 years (range =19-77) for the negative group. Mean disease duration was 74 months (range =2-234) and 54 (range =3-246) respectively. There was no statistically significative difference between gender, age and disease duration between both groups. The positivity of anti-α-fodrin antibodies was significantly associated with low C4 levels (27% vs. 0%, p=0.01), polyclonal hypergammaglobulinemia (68% vs. 33.3%, p=0.03) and minor salivary gland biopsy positivity (31.8% vs. 5.5%, p=0.04). Neither glandular nor any systemic manifestation of pSS was associated with seropositivity for anti-α-fodrin antibodies. The titers of anti-α-fodrin levels were not associated with systemic involvement. Conclusions: The frequency of anti-α-fodrin antibodies in patients with pSS was 55% and significantly different from healthy controls. The patients who tested positive for these antibodies had a significantly higher frequency of hypergammaglobulinemia and hypocomplementemia. Due to the considerable frequency of anti-α-fodrin found in our population, and its correlation with serological markers of pourer outcome, its detection may prove to be a useful and sensitive tool in those patients with pSS seronegative for anti-Ro/SS-A and anti-La/SS-B. Disclosure of Interest: None declared